Gambaran Kepatuhan Penderita Hipertensi Di Puskesmas Ngaliyan Kota Semarang Dengan Pendekatan Social Cognitive Theory (SCT) - Gloria, Fransisca; Safrida, Safrida; Dahliyanti, Novita Dwi; Vidiani, Anak Agung Pradnya Paramitha; Suwarni, Sri (Jurnal Farmasi & Sains Indonesia, 2025)
Based on the 2018 Riskesdas, the prevalence of hypertension in Indonesia was 34.1%, where Central Java reached 37.57%, and Semarang City ranked first at 19.56%. Hypertension is a major risk factor for cardiovascular disease that occurs when a person's blood pressure is 140/90 mmHg or more, also due to patient's non-compliance in taking medication. This study aims to determine the picture of compliance in patients with hypertension using the Social Cognitive Theory (SCT) approach. This observational study used a cross-sectional method with the Hill-Bone and SCT compliance questionnaires. This study was conducted at the outpatient pharmacy service of the Ngaliyan Health Center in Semarang City in the period March-May 2024 with a total of 145 respondents. The results obtained were that the level of compliance in taking medication for hypertension patients mostly had a moderate level of compliance of 100 respondents (69%), while respondents who had a low level of compliance were 30 respondents (21%) and those who had high compliance were 15 respondents (10%). The results of the SCT approach showed that most hypertension sufferers were in the high category with 56 respondents (47%), the moderate category with 68 respondents (47%), and the low category with 21 respondents (14%).